The Effect of Time Pressure, Accountability and Due Profesional Care on Audit Quality - Pradhika Karina Putri; Rizki Amalia Nurvianti (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to obtain emprical evidence about the influence of time pressure, accountability and due profesional care on audit quality Design/methodology/approach – This study uses a quantitive research method, using primary data collected from the population of 85 college students majoring in accounting at Bekasi City University. Data analysis was carried out using Patrial Leas Square (PLS) software with moderated Regression Analysis. Findings – This results of this study found that time pressure has a negative and significant effect on audit quality, accountability has a positive and significant effect on audit quality and due profesional care has a positive and significant effect on audit quality. Research limitations/implications/implications – This research can be an input for auditors and public accounting firm in improving audit quality. This research should also discuss audiotrs ethics. Because ethics is a crucial aspect in maintaining the quality of audits and the integrity of the auditor person